Korean Wave Culture Dalam Video On Demand (Pengaruh Audiens Atas Budaya Korea Dalam Program Variety Show Running Man) - Aditya, Feriz Rizki; Yulistyowati, Irma Mufita; Kurniawati, Yesischa Margaretha Dwi (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
South Korean culture or what can be called the Korean Wave has spread throughout the world, including Indonesia. The Korean Wave itself spreads from various fields, such as songs, drama, language, games, even variety show programs can also be used as intermediaries to spread culture. One of the interesting and unique variety show programs is Running Man. The Running Man program can not only be enjoyed and seen by Korean citizens, but the whole world can also watch it using video streaming technology called Video on Demand (VoD). The method used in this research is descriptive quantitative and descriptive quantitative research, data collection using questionnaires, with young adult subjects aged 16-29 years who have watched Running Man. The research results showed that the results of the questionnaire distribution included 26 respondents in the city of Malang aged around 16 to 29 years. So there are around 96.2% of them who know the variety show program Running Man, there are 92.3% who have watched the variety show program Running Man and there are as many as 7 people watching more than 300 episodes and 9 people watching 1-50 episodes of more than 600 episodes broadcast.